Use of Expansion and Projection in Research Paper - Emeliya Sukma Damanik (VISION, 2018)
This paper focuses on the use of expansion and projection in background study of research paper written by students. This paper adopts Systemic Functional Grammar to pinpoint and analyze the occurrences of Logical Function. Based on the analysis data, it can be found that the student uses expansion in elaboration, extension and enhancement. Then they also use the projection locution. In this case, the projection of idea doesn’t seem in the research paper. The total number also shows that expansion enhancement is the dominant type which occurs in the background study of research paper. From the finding, it can be understood that the student tries to elaborate the idea,  information in detail about what they are intended and reasoning for choosing the study by using relation of elaboration, extension and enhancement to avoid misinterpretation. It also display that the student is very seldom in using of projection locution such reporting idea or quoting. In fact, they are almost did not use this type. However, it has been known that the use of projection is very important for student to see what an expert or research subject say about the importance of their research. Therefore, this study can be used to describe a better understanding for the English learners of logico-semantic, so that the students can be able to write good research paper. Some implications can be implicated in writing and reading academic as well as translators, students and instructors involved in writing and reading pedagogy.